Development of a Simple and Efficient Solution-Phase Parallel Synthesis of Flexible Non-Steroidal Estradiol Mimics - B. Djigoue, Guy; Maltais, Rene; Poirier, Donald (Combinatorial Chemistry & High Throughput Screening, 2014)
An efficient parallel synthesis was designed to provide libraries of estradiol mimics that can potentially interact with different biological targets associated with estradiol-related diseases. Two libraries of 75 members each were synthesized around a non-steroidal core by adding three levels of molecular diversity. Hydroxybenzaldehydes (1st level of diversity), protected as a methoxymethyl ether, first reacted with primary amines (2nd level of diversity) under reductive amination conditions. The resulting secondary amines next reacted with 4-bromo-1,2-epoxybutane to provide epoxide derivatives as precursors of the 3rd level of diversity. Various nucleophiles were then used to open each epoxide. Methyl isocyanate scavenger was finally used to trap out the excess amine and the protecting group was removed by hydrolysis to provide the final compounds.
Keywords: Epoxide opening